Intercomparison of intense cyclogenesis events over the Mediterranean basin based on baroclinic and diabatic influences - Ll. Fita (Advances in Geosciences, 2006)
A large number of high impact cyclones all over the Mediterranean basin have been reported on the data base of the MEDEX project (http://medex.inm.uib.es). A numerical study on the impacts and interactions of baroclinic and diabatic factors is carried out through a PV-based system of prognostic equations for 11 intense MEDEX cyclone episodes occurred in different zones of the basin (Western, Central and Eastern Mediterranean). The main aim of the study is to investigate the possible similarities and differences among the selected cases of the relative weight of the considered cyclogenetic factors on the cyclone evolutions as function of cyclone type and geographical area. A crucial role of the baroclinicity over the Mediterranean zone is obtained in most of the cases. A certain distinction can be also established in terms of the cyclogenesis areas (Africa, Mediterranean Sea, and Alpine region), and between west-central and eastern Mediterranean basins. It is generally observed that the considered baroclinic and diabatic factors cooperate most strongly for the cyclone deepening process when the disturbance reaches the Mediterranean sea.